THE METHODOLOGY OF TEACHING PHYSICS TO SCHOOL STUDENTS AND THE TASKS OF THE TEACHER IN FORMING THEIR TECHNOLOGICAL WORLD VIEW (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
This article shows how to increase the interest of schoolchildren in physics and how to use interesting physical methods during lessons.